Stability of continuous welded rail on steel bridge subjected to thermal loading. (December 2021) - Mubarack, C.K. Ali; Upadhyay, Akhil
Abstract: Continuous Welded Rail (CWR) forms a smooth high-speed rail track. However, its stability has been a cause of worry for being a slender structural element and its tendency to buckle about the weaker axis. Track-Bridge Interaction (TBI) phenomenon results in additional axial rail stress, creating local high-stress zones in the track. Since TBI is the main reason for rail stress and track displacements of CWR on railway bridges, more confidence needs to be developed by quantifying the stability of CWR-on-bridge. In this study, a simplified numerical model is proposed to study the effect of TBI on the stability of CWR-on-bridge due to temperature loading. Boundary elements are utilized to reduce the number of elements in the model. The model predicts the state of the stress in CWR due to thermal loading. Stability analysis of CWR on a single span bridge employing nonlinear buckling analysis reveals a significant influence of TBI on CWR stability. The two critical buckling parameters of CWR, the maximum buckling temperature ( T max ) and safe temperature increase ( T min ), are affected by TBI. T min drops more rapidly compared to T max and needs to be kept below the safe limits to ensure track safety.